KEDUDUKAN HUKUM KEPAILITAN DALAM SISTEM HUKUM BISNIS NASIONAL (Solusi, 2022)
Bankruptcy law is a branch of business law which is currently undergoing very significant development in line with legal and economic developments. where the settlement of debt and credit relations between debtors and creditors is currently no longer resolved through a civil lawsuit but is settled through a commercial court. Therefore, bankruptcy law has a very strategic position in the national business law system. In addition, bankruptcy law as part of the national business law system cannot stand alone, but has close relationships with other legal fields. The areas of law that are closely related to bankruptcy law are contract law, guarantee law, and company law.